1996
DOI: 10.1093/oxfordjournals.aje.a008814
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Change in Self-reported Physical Function among Older Persons in Four Population Studies

Abstract: Change in self-reported physical function was examined using baseline and 5 years of follow-up data between 1982 and 1991 from the four Established Populations for Epidemiologic Studies of the Elderly studies. In East Boston, Massachusetts (n = 3,809), Iowa and Washington Counties, Iowa (n = 3,673), New Haven, Connecticut (n = 2,812), and North Carolina (n = 4,163), noninstitutionalized persons aged 65 years and older were asked a series of questions to assess their physical function: a modified Katz Activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
187
4
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(207 citation statements)
references
References 34 publications
14
187
4
2
Order By: Relevance
“…A large longitudinal study among older non-institutionalised Americans demonstrated a greater decline in physical function with age than suggested by cross-sectional studies. The rate of decline was greater at a more advanced age and in women (Beckett et al, 1996). In the UK Bassey and Harries (1993) also found greater loss of handgrip strength over 4 years (3% per year in men, 5% per year in women) than predicted from baseline data.…”
Section: Handgrip Strengthmentioning
confidence: 93%
“…A large longitudinal study among older non-institutionalised Americans demonstrated a greater decline in physical function with age than suggested by cross-sectional studies. The rate of decline was greater at a more advanced age and in women (Beckett et al, 1996). In the UK Bassey and Harries (1993) also found greater loss of handgrip strength over 4 years (3% per year in men, 5% per year in women) than predicted from baseline data.…”
Section: Handgrip Strengthmentioning
confidence: 93%
“…Gender differences in mobility disability have previously been examined in several studies (Beckett et al 1996;Grundy and Glaser 2000;Oman et al 1999), with most studies in the field reporting a higher prevalence of mobility disability among women, compared to men (Beckett et al 1996). However, a few studies have reported Electronic supplementary material The online version of this article (doi:10.1007/s10433-016-0386-z) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…'1 It is important to note that an average decline in functional status has its specific dynamics; in most studies, a large proportion of the elderly are found to remain stable in their functional status, a smaller proportion decline, and an even smaller, but not unimportant, proportion improve in functional status.7'8'1 [1][2][3][4][5][6][7][8][9][10][11][12][13] Self-rated health is also reported to deteriorate with advancing age, with the same underlying dynamics as the deterioration of functional status,14-l6 but it is less clear whether this relationship holds into old age. Some studies have reported better health ratings among the old-old than among the young-old.…”
mentioning
confidence: 99%